Clinical Data Analysis: A Challenging Career Option to Clinical Pharmacy Students - Shaik, Ramjan (Indian Journal of Pharmacy Practice)
On behalf of the entire team of ijopp, I thank the authors for contributing their articles in this issue, and the reviewers involved in the publication process. This is my first editorial in which I wish to discuss one of the most important areas of drug development process i.e. Data Analysis.